Crafting joy: a phenomenological study of happiness among Malaysian university students - Ahmad Azmi Abdel Hamid Esmaeil,; Ismail Maakip,; Dg Norizah Ag kiflee @ Dziflee @ Dzulkifli,; Murnizam Halik,; Muhammad Idris Bullare, (Penerbit Universiti Kebangsaan Malaysia, 2024)
This study investigates the elusive concept of happiness, a fundamental yet incompletely understood aspect of human experience. Focusing on university students' perspectives, this research aims to shed light on what constitutes happiness. A qualitative methodology was employed, involving interviews with 15 students from a Malaysian public university. The data was analyzed using an interpretivist phenomenological approach, facilitating a deeper understanding of students' subjective experiences and perceptions. The findings reveal two central themes in the students' views of happiness. The first theme emphasizes the individual's role in crafting their happiness, highlighting the significance of personal agency and introspection in defining what happiness means on a personal level. The second theme underscores society's role in fostering individual well-being, encompassing aspects such as providing peace and freedom, reducing stress, and supporting individuals within the community. This research offers both theoretical and practical insights. On a theoretical level, it enriches the existing discourse on happiness, expanding our understanding of this vital human pursuit. Practically, the findings have implications for policies and strategies in education, community development, and psychology aimed at promoting well-being. In the field of psychology, these insights can inform therapeutic approaches and interventions designed to enhance individual and collective happiness. In conclusion, this study provides a valuable perspective on happiness from Malaysian university students, enhancing our comprehension of this complex and significant aspect of human life.